Using digital technologies to improve agricultural production in the Sahel countries of West Africa - (:unkn) unknown (My University, 2024)
Agriculture in the Sahel faces major challenges, but the integration of digital technologies offers encouraging prospects. The aim of the research is to explore how the integration of digital technologies can not only increase productivity, but also transform farmers' interactions with markets. This literature review identifies the benefits of digital technologies, such as precision farming and geographic information systems, while analysing the obstacles to their adoption, including limited access to the Internet, inadequate infrastructure and lack of training. The investigation shows that, despite the opportunities offered by these technologies, their adoption is hampered by financial and awareness challenges, particularly for small-scale farmers, who make up a majority in this part of Africa. The article also proposes strategies to enhance the adoption of digital technologies, highlighting the importance of public-private partnerships and innovation. In conclusion, a successful digital transformation in Sa
Keywords: African Research